Incidence and Description of Autoimmune Cytopenias During Treatment with Ibrutinib for Chronic Lymphocytic Leukemia Autoimmune Cytopenias During Ibrutinib Treatment - Rogers, Kerry A. (Leukemia, 2015)
Chronic lymphocytic leukemia (CLL) is frequently complicated by secondary autoimmune cytopenias (AIC). Ibrutinib is an irreversible inhibitor of Bruton’s Tyrosine Kinase approved for treatment of relapsed CLL and CLL with del(17p). The effect of ibrutinib treatment on the incidence of AIC is currently unknown. We reviewed medical records of 301 patients treated with ibrutinib as participants in therapeutic clinical trials at the Ohio State University Comprehensive Cancer Center between July 2010 and July 2014. Subjects were reviewed with respect to past history of AIC, and treatment emergent AIC cases were identified. Prior to starting ibrutinib treatment, 26% of patients had experienced AIC. Information was available for a total of 468 patient-years of ibrutinib exposure, during which there were six cases of treatment emergent AIC. This corresponds to an estimated incidence rate of 13 episodes for every 1 000 patient-years of ibrutinib treatment. We further identified 22 patients receiving therapy for AIC at the time ibrutinib was started. Of these 22 patients, 19 were able to discontinue AIC therapy. We found that ibrutinib treatment is associated with a low rate of treatment emergent AIC. Patients with an existing AIC have been successfully treated with ibrutinib and subsequently discontinued AIC therapy.